GE_GERICHTE C/7302/2015 vom 11. Mai 2016 - GE Cour de justice (2016)
CONTRAT DE DÉPÔT ; IMPOSSIBILITÉ ; DROIT BANCAIRE ; MANDAT ; DROIT INTERNATIONAL PRIVÉ | CO.119.1 CO.1 CO.397.1 CO6 LDIP.19 LB.3 LFINMA.7